STUDY OF DRAINAGE, PANORAMIC HOUSING, CEMENGKALANG VILLAGE, SIDOARJO DISTRICT - Ismanto, Ikko Bagus; Nugroho, Laksono Djoko; Oetomo, Wateno (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2022)
Panorama Residence housing which has an area of 8000 m2 is located in a plain area with a slope of about 0-1%. The survey results on the Panorama Residence Housing, Cemengkalang Village, Sidoarjo District, have an elevation of -0.20 m, slightly above the flood level – 0.30 m. This area has a high probability of flooding due to overflow from the Pucang River, which runs off (run-off water) from other areas if it rains with high intensity. Moreover, the Panorama Residence area is a dense residential area with roads and parking lots, so rainwater has a smaller chance of infiltrating and running off. After analysis, The flood discharge at the 25-year return period on the Pucang River was 72,561 m3/sec. At the same time, the cross-sectional capacity of the Pucang River was 64,402 m3/sec, so the cross-section of the Pucang River at the Panorama Residence Housing location experienced overflow. The run-off volume is 102.6 m3, while the total capacity is 565.68 m3, so the extended storage capacity is quite adequate. In rainy conditions, t = 30 minutes, the run-off volume that occurs = 30.96 m3, and the total channel length = 493.12 m, the total drainage channel capacity = 184.92 m3 is greater than the run-off volume, 30.96 m3.